Direct numerical simulations of reacting flows with detailed chemistry using many-core/GPU acceleration. (15th September 2018) - Hernández Pérez, Francisco E.; Mukhadiyev, Nurzhan; Xu, Xiao; Sow, Aliou; Lee, Bok Jik; Sankaran, Ramanan; Im, Hong G.
Highlights: A new in-house HPC reacting flow DNS solver, KARFS, is introduced. KARFS implements a MPI+X programming model through the Kokkos library. The model allows performance portability to multi-core, many-core and GPUs. The capability to perform DNS with large, detailed kinetic schemes is demonstrated. Significant acceleration of chemistry integration is achieved by using GPUs. Abstract: A new direct numerical simulation (DNS) code for multi-component gaseous reacting flows has been developed at KAUST, with the state-of-the-art programming model for next generation high performance computing platforms. The code, named KAUST Adaptive Reacting Flows Solver (KARFS), employs the MPI+X programming, and relies on Kokkos for "X" for performance portability to multi-core, many-core and GPUs, providing innovative software development while maintaining backward compatibility with established parallel models and legacy code. The capability and potential of KARFS to perform DNS of reacting flows with large, detailed reaction mechanisms is demonstrated with various model problems involving ignition and turbulent flame propagations with varying degrees of chemical complexities.